Collaboration and Technology 19th International Conference, CRIWG 2013, Wellington, New Zealand, October 30 <U+0013> November 1, 2013, Proceedings - Antunes, Pedro.; Gerosa, Marco Aurľio.; Sylvester, Allan.; Vassileva, Julita.; Vreede, Gert-Jan. (Lecture Notes in Computer Science,, 2013)
This book constitutes the proceedings of the 19th Collaboration Researchers' International Working Group Conference on Collaboration and Technology, held in Wellington, New Zealand, in October/November 2013. The 18 revised papers presented together with 4 progress papers were carefully reviewed and selected from 34 submissions. They are organized into six thematic sessions as follows social media, social networks, crowdsourcing, learning, collaboration design and software development.